Perkembangan Teologi Di Era Moderenisme Dan Dampak Bagi Iman Kristen Masa Kini - Telaumbanua, Yohanes; Pasaribu, Marulak (Sekolah Tinggi Teologi Sriwijaya, 2024)
In the era of information that continues to develop, someone can be influenced by hoax information that has no basis. Social media makes it easy to access information and establish communication (Rohmadi, 2016). A crucial problem that is currently troubling in the digital era is the increasing prevalence of hoax information. Kasperek & Messersmith (2015) stated that hoax information spreads quickly. Hoaxes can mislead and influence public perception so that the information is considered the truth. but also in the understanding that Jesus is not seen as God (Allah) because He had human form and also carried out activities like an ordinary human being (Skepticism) because a wrong understanding of the truth of God's word has fatal consequences in the growth of faith of believers today, including in believing in everything text of God's word. For researchers, it is very important to review the movement and way of thinking of Modernism and a certain picture of the world that was originally inspired by Descartes, which emphasized the concept of